Unique case of 19p13 syndrome with storage pool disease. (28th October 2021) - Liaquat, S; Riley, R; Massey, G; Gunning, W T
Abstract: Introduction/Objective: Microdeletion of a region of the short arm of chromosome 19 results in a very rare syndrome called 19p13.3 deletion syndrome, which manifest itself in developmental delay as well as structural abnormalities such as facial dysmorphism and macrocephaly. Methods/Case Report: We present a case of 14-month-old patient, born at term and was large for her gestational age. She had dysmorphic facial features including posterior cleft palate for which, she required placement of G-tube. Post-delivery, she experienced respiratory distress as well as hypoglycemic episodes. Over the period of time, her mother also noticed occasional bleeding through her gums with teething. Genetic workup was performed, which revealed 2.4 Mb of microdeletion at chromosome 19 region p13.3, including deletion of PIAS4, MAP2K2, GNA11, TBXA2R, RAX2 genes. TBXA2R mutation is associated with bleeding disorder due to a defect in platelet aggregation. The mutation in TBXA2R can lead to platelet type 13 bleeding disorder. For this purpose, a platelet aggregation study was performed to evaluate platelet function disorders. However, the result of the platelet aggregation study was inconclusive as it showed decrease responses to all agonists including arachidonic acid, epinephrine, ADP, collagen and ristocetin. Further work-up by electron microscopy (EM) of platelets (PL) revealed a significant decrease of delta granules (DG) (0.89 DG/PL, normal 4-6 DG/PL), consistent with delta granule storage pool deficiency (δ-SPD). Other abnormalities observed by EM included occasional gray platelets, platelets with immature and/or decreased numbers of α-granules, and rare giant α-granules. Results (if a Case Study enter NA): NA Conclusion: To the best of our knowledge, no other case of 19p13.3 microdeletion syndrome with δ-SPD and associated abnormalities in α-granules has previously been described in the literature. Although it is unclear if there is any relationship between δ-SPD and 19p13.3 deletion syndrome, further investigation is warranted.